Peripheral Adenomatoid Odontogenic Tumour — Is It Really Peripheral?: A Case Report - N. Lavanya; M.R.C. Rajeshwari; R. Bharathi; A. Shaheen (Journal of Clinical and Diagnostic Research, 2013)
A Peripheral Adenomatoid Odontogenic Tumour (PAOT) is quite a rare entity which has been infrequently reported in the literature. These uncommon clinical variants of an Adenomatoid Odontogenic Tumour (AOT), typically manifest as a soft tissue mass of the gingiva, which mimick a common epulis, but yet have an identical histopathologic presentation as their intraosseous counterpart. These lesions, though they are indolent in nature, have a tendency to cause well defined deep bony pockets. Only fourteen cases have been adequately documented so far. We are reporting a case of a PAOT of the anterior maxillary gingiva, with a periodontal bone defect in a 12 year old girl. The relevant literature has been briefly reviewed, with an insight into the probable origin of PAOTs with bony defects.